Pengaruh Minat Baca terhadap Hasil Belajar Kognitif pada Siswa Kelas IV dan V SD YPPK Hati Kudus Kelapa Lima Merauke - Yohanes Hendro Pranyoto; Deposina Djonler (JURNAL PASTORAL KATEKETIK, 2025)
This study aims to determine: (1) the influence of reading interest on cognitive learning outcomes of 4th and 5th grade students at YPPK Sacred Heart Elementary School Kelapa Lima Merauke; (2) the magnitude of reading interest influence on cognitive learning outcomes; and (3) efforts to increase students' reading interest. The research uses a quantitative approach with regression analysis method. The research population included all 36 students in grades IV and V at YPPK Sacred Heart Elementary School Kelapa Lima Merauke. The sampling technique used was population sampling (entire population as sample). The research instrument was a reading interest questionnaire with 30 statements using a Likert scale, while cognitive learning outcome data was obtained from report card scores for the odd semester of the 2023/2024 academic year. The results showed: (1) there is an influence of reading interest on students' cognitive learning outcomes with a significance value of 0.000 < 0.05; (2) the magnitude of the influence of reading interest on cognitive learning outcomes is 31.3% (R² = 0.313), while 68.7% is influenced by other variables not examined; (3) efforts to increase reading interest include: development of school libraries with diverse book collections, implementation of literacy programs, and development of engaging learning methods. The regression equation obtained is Y = 56.759 + 0.172X, which means that each increase of 1 point in reading interest will increase cognitive learning outcomes by 0.172 points.